Correlation Between Teeth Alignment and Oral Diseases in New India - T.A. , Deepak; Tejasvi M.L., Avinash (International Journal of Applied Sciences and Biotechnology, 2023)
Systemic Health goes together with oral health. In India, Oral health remains a big challenge. It is connected tightly to overall individual’s health. Basic oral hygiene such as brushing teeth twice a day is still foreign to most, while such practices are widely practiced in the west. In India, economic factors, coupled with normally accepted behavior and acceptance of poor oral hygiene, prevention of awareness contributed to vast populace with dental issues, like cavities, gum diseases, premature teeth loss, and oral cancers in some cases. With almost 60% of 1.4 billion living in rural areas, initiatives like oral hygiene awareness, preventative care, lifestyle changes and increased dental facilities including universities, colleges and dental care facilities are needed today.We investigate whether there is an association between awareness of teeth alignment, good oral health to overall systemic health. We developed a questionnaire for dental patients falling between the age of 13 - 21 years. This range was selected as most of the patients are old enough to know their oral habits, and other health issues. The patient’s data was collected over a range of 8 months (April 2023 to November 2023) between two states in southern India. The research had 191 patients who were from rural areas, and their awareness on oral hygiene activities were found to be far worse than their urban counterparts (both genders). Based on the data collected, we establish a close relationship between awareness of teeth alignment, to gum bleeding, caries, and pollinosis in young Indians.Int. J. Appl. Sci. Biotechnol. Vol 11(4): 209-216.